Effects of energy supply and nicotinic acid supplementation on serum anti‐oxidative capacity and on expression of oxidative stress‐related genes in blood leucocytes of periparturient primi‐ and pluriparous dairy cows. Issue 1 (25th April 2017) - Bühler, S.; Frahm, J.; Tienken, R.; Kersten, S.; Meyer, U.; Huber, K.; Dänicke, S.
Summary: The periparturient period is accompanied by metabolic and oxidative stress. Niacin is known to decrease lipolysis but is also reported to have anti‐oxidative effects. Therefore, we examined the effects of energy supply and a nicotinic acid (NA) supplementation on anti‐oxidative serum parameters and on the expression of oxidative stress‐related genes in blood leucocytes of periparturient dairy cows, differing in parity. Twenty‐nine pluriparous and 18 primiparous cows were allocated to four different feeding groups 42 days before expected parturition until 100 days postpartum and fed a ration with either a low concentrate proportion of 30% (LC) or a high concentrate proportion of 60% (HC). After parturition, all animals received 30% concentrate which was increased to 50% either within 16 (LC group) or 24 days (HC group). Half of the animals per group were supplemented with 24 g NA per day from 42 days prepartum until 24 days postpartum. All investigated parameters varied significantly over time compared to parturition ( p  < .05). Ferric reducing ability (FRA) exhibited a nadir before parturition, and the antioxidant enzymes glutathione peroxidase (GPX) and superoxide dismutase (SOD) showed peak activities around parturition. Expression levels of GPX1, SOD2, xanthine dehydrogenase (XDH) and nuclear factor (erythroid‐derived 2)‐like 2 (NRF2) peaked before calving. The concentrate level influenced GPX activity and mRNA abundance of SOD2, XDH and poly (ADP‐ribose) polymerase 1 (PARP1). Pluriparous animals exhibited higher serum GPX activities, a more distinct nadir for FRA and higher expression levels for GPX1, SOD2 and XDH. Primiparous cows displayed higher serum SOD activities. NA supplementation increased serum SOD activity antepartum in LC animals. Parturition was characterised by an increased need for antioxidants and an increased expression of oxidative stress‐related genes that clearly differed with parity and was influenced by energy supply while NA exerted only minor effects on the investigated parameters.